National Evaluation of the Juvenile Accountability Incentive Block Grant Program, 1998-2002 - Parent, Dale ([Verlag nicht ermittelbar], 2006)
This study examined the operation of the Juvenile Accountability Incentive Block Grant program (JAIBG) from fiscal years 1998 through 2000. In order to describe how states implemented the JAIBG program, this study examined the program's effects on state and local juvenile justice policies and practices, which included studying how states awarded the grant funds to localities and for what purposes, and an assessment of how states changed their policies and practices during this period. Variables in Part 1 (Juvenile Accountability Incentive Block Grant (JAIBG) Subgrant Follow-Up Information Form Data) provide grant information, jurisdiction type, planning typology of state, amount of funds budgeted for administrative purposes, and for each of 12 purpose areas, total amount of funds spent in subgrant, and number of the various entities involved in juvenile crime prevention. Variables in Part 2 (Fiscal Year 1998 Supplemental Programmatic Information Form Data) provide grant information, jurisdiction type, planning typology of state, type of program, primary purpose of funded programs in each of the 12 purpose areas (if the funds supported a new program in that purpose area), as well as allocation of funds and total funds in each purpose area. Variables in Parts 3-5 (Perceptions and Attitudes About the JAIBG Program Survey Data for JAIBG Subgrant Recipients, Perceptions and Attitudes About the JAIBG Program Survey Data for State Juvenile Crime Enforcement Coalition (JCEC) Members, and Perceptions and Attitudes About the JAIBG Program Survey Data for Local Juvenile Crime Enforcement Coalition (JCEC) Members) provide state, planning typology of state, and recipient's professional affiliations (by category). The surveys also included questions to measure the recipient's satisfaction with the JAIBG program and the funding received. Data available in this collection were obtained from the following two sources: (1) data collected by Follow-Up Information Forms (FIFs) for fiscal years 1998, 1999, and 2000 (Part 1), and (2) mail survey data collected by Abt Associates Inc., which included: programmatic and financial data for a sample of fiscal year 1998 programs (Part 2), attitudinal and opinion surveys of a sample of subgrant recipients (Part 3), state Juvenile Crime Enforcement Coalition (JCEC) members (Part 4), and a sample of local JCEC members (Part 5).